Integrating Task-Based Learning and ICT in Reading and Writing Classes in Hybrid Setting - Pratiwi, Damar Isti; Anggraeni, Candradewi Wahyu; Tristiana, Novita Eka; Amumpuni, Rengganis Siwi; Sholikhah, Masriatus (Journal of Education Reseach and Evaluation, 2023)
Several ICT tools are chosen as media in reading and writing courses, such as socrative for practicing and testing vocabulary, google form for practicing and evaluating reading ability, and writeabout for practicing students' writing skills based on given topics. The study analyze classroom practices of a reading and writing course in hybrid setting which integrated Task-Based Learning (TBL) and Information and Communication Technologies (ICT). It is a case study with quantitative approach. This project was done in 6 classes of reading and writing course consisted of 159 students in total. The data was gathered through classroom observation, pre-, and post-test scores analysis, and questionnaire analysis about students' feedback. The pre-and post-test scores were analyzed using descriptive statistical analysis, paired sample t-test, and changing level analysis.The findings indicated that teachers integrated TBL and various ICT tools to accomplish the course description and objectives. The result of those three data analyses described significant improvement in students' learning outcomes. The course received positive responses from the students with a 4.02 out of 5 (good level). The integration of TBL and ICT in a reading and writing course is considerable in enhancing students' achievement and enjoyment in hybrid setting. This study provided benefit from insight into the knowledge and practice for reading and writing lecturers to integrate TBL and ICT in their instruction particularly in hybrid context.